Explore the Application of Machine Learning in Image Recognition and Detection - Xu, Junyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the rapid development of computer technology, the application of image recognition technology and machine learning technology in society has become more and more proven. Through consulting a large number of data and literature, this paper probes into the development status of image recognition technology and its future development trend and shortcomings. This paper concludes that there is a certain advanced technology development at present, and machine learning and image recognition are slowly being applied in many fields. For example, it has applications in the fields of medical pathology examination, unmanned supermarkets, autonomous driving and intelligent monitoring. However, some problems are related to low precision, insufficient intelligence, and privacy, which need to be solved in future development and application. In the future, the application of machine learning in image recognition has great space for development and a large market. This article can help others learn the relevant knowledge and suggest some directions and trends to solve the problem.